Italian-Canadian Family Items as Domestic Objects of a Diaspora - Niccoli, Gabriel (Italian Canadiana)

(untitled) (Iter Press, 2024)
This article examines, through a long series of interviews carried out mostly within the Italian diaspora of the Waterloo region of southwestern Ontario yet virtually applicable to the rest of the country, the salient characteristics diasporic domestic objects display vis-à-vis their privileged interlocutors, their family custodians. Supported by an array of theoretical views on the object per se, the study intends to explore more fully both the symbolic valence and the identity charge palpable objects of diaspora, often of domestic nature, might have retained for their custodians. It aims to probe and identify the sense and silence of these objects as they continue to engage in dialogue with their Italian-Canadian keepers, particularly those who, while continuing to live in Canada, have maintained through generations a strong sense of their Italian roots.